Experiências estéticas e cognitivas mediadas por imagens digitais - Klem, Dilma Marques Silveira (2013)
The present work is guided by the question in respect of how the digital images have mediated esthetic and cognitive experiences. The context chose for the developing of the research is in the professors and students relationship in the Visual Arts graduation course in the EaD model. The research is made in the course of Graduation in Visual Arts – UAB/Unimontes. An investigative process that propose an analysis doing references to the technological images and your appropriation on the process of teaching-learning, investigating how these images was used by the professors of the specific disciplines in the course and how it was assimilated by the students. It‟s an object that requires study to reveal the relations between these images, possibilities and potentialities as a mediator in your multiples forms of expression. The group of people involved in this research is constituted by two professors of the respective disciplines, three tutors and four students from the course of Lagoa Santa, totalizing a universe of nine people involved directly. The conceptual categories, that are considered epistemological axes, are: visual culture, digital image, TICs, EaD, digital learning environment, esthetic and artistic experience. The approach of these concepts makes the delimitation of the camp where the digital images mediations in the process of the visual poetic happened, articulating theory and practice. The pinnacle of the research allowed some perceptions like: the digital technologies are not absolutes or totalitarians, on the contemporary culture, remaining territory transits between digital and physic space, a hybrid relation between plastic material and visual medias.